Solution Phase and Nanoparticular Biosynthetically Inspired Interconnections in the Canthin‐6‐one β‐Carboline Series and Study of Phenotypic Properties on C. elegans. Issue 26 (29th July 2013) - Cebrián‐Torrejón, Gerardo; Mackiewicz, Nicolas; Vázquez‐Manrique, Rafael P.; Fournet, Alain; Figadère, Bruno; Nicolas, Julien; Poupon, Erwan
Abstract: Based on the biosynthetic line of canthin‐6‐one alkaloids from their simple precursors such as tryptamine, the present work is focused on the study of alternative protocol of the Bischler‐Napieralski reaction and has led to a full coverage of the different biosynthetic intermediates. Nanoparticles were also prepared as mimics of biosynthetic assembly lines and some interesting biological results in term of chemical ecology are also reported. Abstract : Canthin‐6‐one, a particular representative β‐carboline alkaloid, was targeted for synthesis keeping in mind its biosynthetic origin. In fact, several biosynthetic intermediates were synthesized and nanoparticular mimicry of key steps was also achieved permitting further evaluation of biological properties for this class of alkaloids.